2016
DOI: 10.1111/evo.12858
|View full text |Cite
|
Sign up to set email alerts
|

Fisher's geometric model predicts the effects of random mutations when tested in the wild

Abstract: Fisher's geometric model of adaptation (FGM) has been the conceptual foundation for studies investigating the genetic basis of adaptation since the onset of the neo Darwinian synthesis. FGM describes adaptation as the movement of a genotype toward a fitness optimum due to beneficial mutations. To date, one prediction of FGM, the probability of improvement is related to the distance from the optimum, has only been tested in microorganisms under laboratory conditions. There is reason to believe that results migh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…In the more benign conditions of the growth room, the difference between founder and mutant lines was much less pronounced. Previous work on an earlier generation of these mutant lines derived from EMS mutagenesis found a similar result: In two of three field plantings, mutations reduced fitness on average relative to the founder (Stearns & Fenster, 2016). …”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In the more benign conditions of the growth room, the difference between founder and mutant lines was much less pronounced. Previous work on an earlier generation of these mutant lines derived from EMS mutagenesis found a similar result: In two of three field plantings, mutations reduced fitness on average relative to the founder (Stearns & Fenster, 2016). …”
Section: Discussionmentioning
confidence: 55%
“…This has been corroborated experimentally (Davies, Peters, & Keightley, 1999) and most recently by Heilbron, Toll‐Reira, Kojadinovic, and MacLean (2014) who found that 42.3% of the decrease in fitness in Pseudomonas aeruginosa mutation accumulation lines was explained by only 4.5% of the mutational steps that had a highly deleterious effect on fitness, only 0.5% of all mutations fixed. Previous work with an earlier generation of these mutant lines (and the mutant lines of several other A. thaliana ecotypes) suggested that beneficial mutations occurred, but that the magnitude of deleterious mutations was greater (Stearns & Fenster, 2016). This study, when considered in the context of the previous A. thaliana mutation accumulation studies, suggests that high magnitude deleterious mutations are more common than high magnitude beneficial mutations and that adaptation likely occurs due to small or intermediate effect beneficial mutations, as suggested by Fisher (1930) and Kimura (1983) and supported experimentally (Barrett, MacLean, & Bell, 2006; Heilbron et al., 2014; Sousa, Magalhaes, & Gordo, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the assayed population may be far from its optimum in the new environment, increasing the likelihood a mutation will be beneficial, as has been observed with experimental studies of microorganisms (Burch & Chao, 1999; Khan, Dinh, Schneider, Lenski, & Cooper, 2011; Kryazhimskiy, Rice, Jerison, & Desai, 2014; MacLean, Perron, & Gardner, 2010; Perfeito, Sousa, Bataillon, & Gordo, 2014) and in one field study with A. thaliana (Stearns & Fenster, 2016). It is also possible that there was within‐plant selection during the propagation of the mutation accumulation lines (Otto & Orive, 1995).…”
Section: Discussionmentioning
confidence: 84%
“…If we scale up our estimates of V g to 25 generations of MA, then mutations have contributed on the order of 2 × 10 −3 V g scaled to V e for fitness. In contrast, studies of accessions grown in fieldlike settings, or RILs generated from an extreme cross of Italian and Swedish A. thaliana populations, similarly measured for fitness or fitness proxies found V g scaled to V e is much higher, on the order of 0.05-0.1 (Ågren, Oakley, McKay, Lovell, & Schemske, 2013;Rutter & Fenster, 2007;Samis et al, 2012;Stearns & Fenster, 2016), as one might expect. However, to put this into the context of mutational contributions to fitness variance, after only 25 generations of MA, the 100 lines have diverged such that this population of 100 MA lines has on the order of 25-fold less fitness variation than found in a survey of 21 worldwide A. thaliana accessions grown at a single site (Rutter & Fenster, 2007).…”
Section: Calibration Of Mutational Variance With Standing Genetic Vmentioning
confidence: 76%
See 1 more Smart Citation